Konsep Pendidikan Islam Nusantara Perspektif Helmy Faisal Zaini - Siti Halimah; Jakaria Umro; Syarifatul Isti Inayah (JIE (Journal of Islamic Education), 2023)
Religious education with the concept of Islam Nusantara will be more accepted by society because it gives an understanding that the media used is part of oneself. The realm of Nusantara Islamic education is education in which there is Islam which focuses on maintaining local culture. According to Helmy Faisal Zaini, the practice of Nusantara Islamic education is pesantren education. So that the focus of this research is on the concept of education. The research method used is literature study. Sources of data can be obtained through books by Helmy Faisal Zaini as the primary source, and journals or papers as supporting data sources. Data analysis, the researcher uses Miles and Huberman's theory, includes three streams of simultaneous activity: data reduction, data presentation, and conclusions. The results obtained from Helmy Faisal Zaini's thoughts are that the roots of Nusantara Islamic education are pesantren, because pesantren are educational institutions that do not abandon regional traditions or local culture, and are also the development of science and culture with a religious dimension in the archipelago.